2007
DOI: 10.1016/j.jacc.2006.08.054
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effects of Pioglitazone and/or Simvastatin in High Cardiovascular Risk Patients With Elevated High Sensitivity C-Reactive Protein

Abstract: Pioglitazone, probably by reducing insulin resistance, has additive anti-inflammatory effects to simvastatin in non-diabetic subjects with CVD and high hs-CRP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
116
2
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(129 citation statements)
references
References 48 publications
8
116
2
3
Order By: Relevance
“…Lung function as quantified by FEV 1 (liters) was lowest in the overweight/obese subjects with asthma (P ¼ 0.022 compared with lean asthma; P ¼ 0.034 compared with obese normal). No subjects took statins or thiazolidinediones, which could have a potential antiinflammatory effect (23)(24)(25). Twenty-two subjects were included in the ex vivo experiments and the characteristics of this cohort are included in Table 2.…”
Section: Subject Characteristicsmentioning
confidence: 99%
“…Lung function as quantified by FEV 1 (liters) was lowest in the overweight/obese subjects with asthma (P ¼ 0.022 compared with lean asthma; P ¼ 0.034 compared with obese normal). No subjects took statins or thiazolidinediones, which could have a potential antiinflammatory effect (23)(24)(25). Twenty-two subjects were included in the ex vivo experiments and the characteristics of this cohort are included in Table 2.…”
Section: Subject Characteristicsmentioning
confidence: 99%
“…Moreover, CRP directly facilitates the development of cardiovascular disease by decreasing nitric oxide synthesis and inducing adhesion molecule expression in human endothelial cells [17,18]. Recently, CRP was reported to be independently associated with short-term mortality risk in type 2 diabetes mellitus patients [19]; and several studies have shown that pioglitazone reduces plasma CRP levels [3][4][5][6][7][8][9][10][11][12][13]. Moreover, 16 weeks of pioglitazone treatment decreased CRP levels by 42% in type 2 diabetes mellitus patients [12]; and pioglitazone further reduced CRP in patients with hypertension and diabetes who were receiving angiotensin II receptor blockers [5].…”
Section: Discussionmentioning
confidence: 99%
“…reduction of proinflammatory markers including C-reactive protein (CRP) [3][4][5][6][7][8][9][10][11][12][13]. C-reactive protein is an acute-phase reactant that is known as a proinflammatory marker and a predictor of cardiovascular events [14][15][16].…”
mentioning
confidence: 99%
“…The inconsistent results may reflect the relatively small number of patients on pioglitazone; however, previous studies suggest beneficial effects. [21][22][23][24][25][26] Its use in patients with ESRD and diabetes will be the subject of future DOPPS analyses once additional data become available.…”
Section: Discussionmentioning
confidence: 99%